2016
DOI: 10.1186/s12891-016-0913-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-fusion procedure using PEEK rod systems for lumbar degenerative diseases: clinical experience with a 2-year follow-up

Abstract: BackgroundPolyetheretherketone (PEEK) rod system is a novel pedicle-based dynamic stabilization system. This study evaluated clinical and radiographic outcomes of non-fusion surgery by PEEK rod systems for treatment of degenerative lumbar diseases with a 2-year follow-up.MethodsFrom February 2012 to October 2012, 38 patients who underwent non-fusion surgery using PEEK rod systems were included in the study. Data on Oswestry Disability Index (ODI) score and Japanese Orthopaedics Association (JOA) score were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 33 publications
3
29
0
Order By: Relevance
“…Previous large series of PEEK rod use have not reported on the long-and mid-term results. For smaller patient groups, presented outcomes usually refer to an approximate 2-year follow-up (5,12,13, 15,18,26). To the best of our knowledge, the largest patient series to date has been published by Athanasakopoulos et al, including 52 patients (5).…”
Section: A B Cmentioning
confidence: 99%
“…Previous large series of PEEK rod use have not reported on the long-and mid-term results. For smaller patient groups, presented outcomes usually refer to an approximate 2-year follow-up (5,12,13, 15,18,26). To the best of our knowledge, the largest patient series to date has been published by Athanasakopoulos et al, including 52 patients (5).…”
Section: A B Cmentioning
confidence: 99%
“…Additionally, at the final follow-up, the Pfirrmann grades of the adjacent segment of the 2 groups were not different (P � 0.346; P � 0.125). Huang W et al reported that 38 patients who underwent fixation with a PEEK rod did not experience ASD [11] and that patients who underwent fixation with a PEEK rod did not have an increased incidence of ASD. Fay et al found that younger patients with Pain Research and Management dynamic fixation had rehydration of the disc after surgery [23].…”
Section: Discussionmentioning
confidence: 99%
“…Polyetheretherketone (PEEK) rods are widely used as semirigid fixation systems for nonfusion fixation of the spine [8,9]. ese rods can effectively maintain the height of the intervertebral space without the adjacent segment disease (ASD) caused by rigid fixation [10,11]. erefore, we used the PEEK rod semirigid fixation system for the treatment of giant disc herniation.…”
Section: Introductionmentioning
confidence: 99%
“…Stabilization with PEEK rods was also demonstrated to bear a very low risk of screw loosening or breakage. 19,20…”
Section: Study Impact and Its Implicationsmentioning
confidence: 99%